Strategi Pengembangan Usaha Terhadap Kinerja Pemasaran Usaha Home Lavacakery pada Covid-19 - Sinta Nur Rahmadana; Saida Zainurossalamia ZA (MAMEN: Jurnal Manajemen, 2023)
The purpose of this study is to explain the strategies applied to the Lavacakery business in business development towards marketing performance during the Covid-19 period. The type of research used is descriptive qualitative. In this study, the data used was data derived from primary and secondary data using a SWOT analysis tool. The data collection technique carried out was by observation, interviews, documentation, and dissemination of questionnaires to Lavacakery consumers, totaling 65 respondents. The results of this study obtained a total score from the IFAS factor and EFAS strength having a total score of 2.973, weakness of 0.47, odds of 2.47, and threats of 1.130. And it is known that the difference in the total score factor of strength and weakness is (+) 2.503, while the difference in the total score of opportunities and threats (+) is 1.34. The results show that through the SWOT diagram, the Lavacakery Business is in quadrant I, namely SO, namely in the application of various business developments carried out by Lavacakery can maximize the strength of the company in order to seize various opportunities so that it can balance competitors.